Perlindungan Hukum Pemegang Protokol Notaris atas Akta Yang Menjadi Gugatan di Pengadilan Negeri Yogyakarta - Daud, Akbar Hidayatullah (Faculty of Law Universitas Islam Indonesia, 2024)
This study discusses first, the form of legal protection for holders of notary protocols for deeds that become lawsuits in the Yogyakarta district court; and second, the responsibility of the holder of the notary protocol for the deed that became a lawsuit in the Yogyakarta district court. The type of research used is normative by using a doctrinal or conceptual approach and qualitative data analysis. The results of this study conclude, first, the form of protection for notary protocol holders when problems occur in the future is protected in UUJN and UUJNP where the mechanism for examining notaries by judges, prosecutors, and the police against notaries holding notary protocols is through the Notary Honorary Council (MKN) in other words, waiting for approval from the MKN first. Second, the responsibility of the notary protocol holder is only limited to the protocol he issued, in the form of a gross deed, a deed excerpt, and a copy of the deed. One time there is a problem with the deed that becomes the protocol, the notary holding the protocol has no responsibility for the deed previously made by the notary and the parties concerned.Keywords: legal protection, notary protocol, responsibility AbstrakPenelitian ini membahas terkait pertama, bentuk perlindungan hukum terhadap pemegang protokol notaris atas akta yang menjadi gugatan di pengadilan negeri Yogyakarta; dan kedua, tanggung jawab pemegang protokol notaris atas akta yang menjadi gugatan di pengadilan negeri Yogyakarta. Jenis penelitian yang digunakan adalah normatif dengan memggunakan pendekatan dokrinal atau konseptual serta Analisa data secara kualitatif. Hasil penelitian ini menyimpulkan, pertama, bentuk perlindungan bagi pemegang protokol notaris ketika terjadi permasalahan dikemudian hari dilindungi dalam UUJN dan UUJNP yang dimana mekanisme untuk pemeriksaan notaris oleh hakim, jaksa serta kepolisian terhadap notaris yang memegang protokol notaris dengan melalui Majelis Kehormatan Notaris (MKN) dalam arti kata lain menunggu persetujuan dari MKN terlebih dahulu. Kedua, tanggung jawab pemegang protokol notaris hanya sebatas protokol yang dia keluarkan, berupa grosse akt, kutipan akta dan salinan akta. Suatu saat terjadi permasalahan terhadap akta yang menjadi protokolnya, maka notaris yang memegang protokol tersebut tidak memiliki tanggung jawab terhadap akta yang telah dibuat sebelumnya notaris dan para pihak yang bersangkutan.Kata kunci: perlindungan hukum, protokol notaris, tanggung jawab